Effectiveness of community mobilisation and groupbased interventions for preventing intimate partner violence against women in low- and middle-income countries: A systematic review and meta-analysis - Leight, Jessica; Cullen, Claire; Ranganathan, Meghna; Yakubovich, Alexa (International Society of Global Health, 2023)
Background Intimate partner violence (IPV) is a challenge affecting one in three women in their lifetime, and gender-transformative interventions have been identified as a promising prevention strategy. We systematically reviewed and meta-analysed randomised controlled trials (RCTs) of community-level or group-based interventions to prevent IPV in lower- and middle-income countries, seeking to answer the following research question: do community- or group-based gender-transformative interventions reduce IPV, compared to a control arm of status-quo programming? Methods We conducted a systematic search from the inception of all databases employed until 20 July 2021. Eligible study outcomes included past-year experience of physical, sexual, emotional or economic IPV self-reported by women and perpetration of physical or sexual IPV self-reported by men. We assessed study risk of bias using the updated Cochrane tool for RCTs. We estimated the pooled odds ratio (OR) using a multilevel random-effects meta-analysis and also conducted a multilevel meta-regression to analyse how study characteristics moderated the effect size. Results After screening 7363 unique records, we included 30 studies on 27 unique RCTs. Our meta-analysis suggested that community-level or group-based interventions reduced the odds of women experiencing IPV in the past year: pooled adjusted odds ratio (aOR) = 0.78; 95% confidence interval (CI) = 0.63-0.97. While there was significant heterogeneity in the effect sizes between trials (I2 = 83%), potentially reflecting the diverse contexts of the included trials, our meta-regression did not indicate a significant association between intervention effectiveness and intervention type or target population. There was evidence of significant associations between effectiveness and intervention components and duration. Discussion There is strong evidence that community-level and group-based interventions reduce IPV against women. Unpacking what intervention modalities are effective in which contexts can further inform prevention strategies.